SOS1 Gain-of-Function Variants in Dilated Cardiomyopathy. (August 2020) - Cowan, Jason R.; Salyer, Lorien; Wright, Nathan T.; Kinnamon, Daniel D.; Amaya, Pedro; Jordan, Elizabeth; Bamshad, Michael J.; Nickerson, Deborah A.; Hershberger, Ray E.
Abstract : Background: Dilated cardiomyopathy (DCM) is a genetically heterogeneous cardiac disease characterized by progressive ventricular enlargement and reduced systolic function. Here, we report genetic and functional analyses implicating the rat sarcoma signaling protein, SOS1 (Son of sevenless homolog 1), in DCM pathogenesis. Methods: Exome sequencing was performed on 412 probands and family members from our DCM cohort, identifying several SOS1 variants with potential disease involvement. As several lines of evidence have implicated dysregulated rat sarcoma signaling in the pathogenesis of DCM, we assessed functional impact of each variant on the activation of ERK (extracellular signal-regulated kinase), AKT (protein kinase B), and JNK (c-Jun N-terminal kinase) pathways. Relative expression levels were determined by Western blot in HEK293T cells transfected with variant or wild-type human SOS1 expression constructs. Results: A rare SOS1 variant [c.571G>A, p.(Glu191Lys)] was found to segregate alongside an A-band TTN truncating variant in a pedigree with aggressive, early-onset DCM. Reduced disease severity in the absence of the SOS1 variant suggested its potential involvement as a genetic risk factor for DCM in this family. Exome sequencing identified 5 additional SOS1 variants with potential disease involvement in 4 other families [c.1820T>C, p.(Ile607Thr); c.2156G>C, p.(Gly719Ala); c.2230A>G, p.(Arg744Gly); c.2728G>C, p.(Asp910His); c.3601C>T, p.(Arg1201Trp)]. Impacted amino acids occupied a number of functional domains relevant to SOS1 activity, including the N-terminal histone fold, as well as the C-terminal REM (rat sarcoma exchange motif), CDC25 (cell division cycle 25), and PR (proline-rich) tail domains. Increased phosphorylated ERK expression relative to wild-type levels was seen for all 6 SOS1 variants, paralleling known disease-relevant SOS1 signaling profiles. Conclusions: These data support gain-of-function variation in SOS1 as a contributing factor to isolated DCM. Abstract : Supplemental Digital Content is available in the text.